The Post-buckled Failure of Steel Plate Shear Webs With Centrally Located Circular Cut-outs. (November 2016) - Loughlan, J.; Hussain, N.
Abstract: This paper examines the response of steel plate shear webs when subjected to in-plane shear loading in the form of applied in-plane shear displacements. The buckling and post-buckling failure capabilities of thin plates subjected to in-plane shear can be substantially eroded through the introduction of openings or cut-outs which can contribute, significantly, towards a less stable structural system. The paper details appropriate suitable finite element modelling strategies and solution procedures to enable the determination of the post-buckled failure response of steel plate shear webs with cut-outs. The results presented in the paper give a detailed account of the complete loading history of the shear webs, illustrating the significant degrading influence on structural performance of the cut-outs and highlighting the importance of the in-plane boundary conditions at the plate edges on the mechanics of structural failure.